WORD BUILDING FIELD OF BORROWED NOUNS OF THE LEXICAL CORE OF MODERN ENGLISH - Razuvaeva, T.N. (Russian Linguistic Bulletin, 2020)
The article covers the study of the word building field of borrowed nouns of American English lexical core. Modern English, with its specific features is the product of a number of eras. Because the development of the language -all aspects of it, including its vocabulary-is gradually taking place, we find in the vocabulary of Modern English words formed in different historical epochs, as a result of different ways of enriching it to different moments of English history. At the moment, the problem of describing the vocabulary composition of the language is in the focus of linguists' attention. Of particular interest is the problem of identifying and describing the lexical core of modern English. The article focuses on the etymological and structural characteristics of the nouns borrowed into English from more than 38 languages The study's relevance is due to the ambiguity of interpretation of the etymological composition of Modern English. The study of the etymological composition of the lexical nucleus may contribute to solving this problem. The author analyses the ways of word formation which comprise the core and periphery of the field. The special attention is given to the most productive word building patterns of each way of word formation by means of which the borrowed nouns were created.